ROME-ARMENIA RELATIONS DURING THE REIGN OF TIGRANES II - Özlem GENÇ (Fırat University, 2019)
History of the Armenian people in Anatolia dates back to time immemorial. Although many leaders took the lead in this ancient history, their most known sovereign is Tigranes II with the epithets of “Great” and “King of Kings”. Having no information about his childhood, the first information about Tigranes is that he was taken hostage at small ages. Ascending the throne as soon as his hostage life had finished, Tigranes extended the land of Armenia much broader with the conquests and the policies he followed. Even if the line of descent he had with Pontus King Mithridates helped them to be successful by acting in unison at first, later on the hostility between Mithridates and the Roman Empire involved Tigranes in and Tigranes came up against the Roman Empire. Losing the wars waged, the Armenian leader had to get back the lands he conquered and retreat to the ancestral borders of Armenia and from that day forward, continued to live as a staunchest ally of Roma. It is seen that he was an open-minded leader, who was interested in Hellenic and Greek cultures.